EVALUATING THE DETERMINANTS OF NATIONAL INNOVATIVE CAPACITY AMONG EUROPEAN COUNTRIES - Maria Manuela Natario; Joao Pedro Couto; Ascensao Maria Braga; Teresa Maria Tiago (European Regional Science Association (ERSA), 2010)
Innovative capacity has a decisive and crucial role in determining who is prospering in the global arena. Innovation is the base for the development of strategic advantages in companies, so necessary in the current context of global competitiveness. Innovative capacity enables countries to increase their productivity and attract investments, thereby sustaining continuous progress in the quality and standard of living. The national economic capacity of a country depends on institutional efficiency, its national culture, and its innovation framework. This paper reflects upon the factors that influence national innovative capacity, based on the European Innovation Scoreboard database. The aim is to reflect and evaluate the factors with influence in national innovative capacity. In this sense, we analyze innovative capacity in terms of innovative output and identify the main factors which differentiate the dynamics of the countries. Clusters analysis was performed to verify how different countries are positioned in terms of innovation outputs and determine which factors distinguish their level of innovative capacity. The results point to the existence of four groups of countries, and the factors identified are related to dimensions of institutional efficiency, namely efficiency of institutions, type of regulation, effective rule of law and level of corruption; the societies' cultural values associated with the level of hierarchy or "power distance" and "uncertainty avoidance" and with aspects related to the innovation framework such as doctorates in science and engineering, business R&D expenses, and level of collaboration for innovating.
Keywords: 330; Innovative Capacity; Innovation; National Culture; Institutional Efficiency; Innovation Infrastructure